Study of The Validity and Reliability of Nanotechnology Awareness Scale in Turkish Culture - Figen Erkoç; Ali Derya Atik; Şeref Tan; Zeki Ipek (International Journal of Assessment Tools in Education)
The aim of this study was to determine the validity and reliability of the Nanotechnology Awareness Scale (NAI) in Turkish culture. The study group consists of 624 biology, physics and chemistry teachers working in secondary schools in Antalya, Denizli, Burdur and Ankara. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were conducted in order to determine its structural validity. Cronbach-alpha and stratified-alpha coefficient values were calculated for the reliability of the sub-dimensions and the whole of the scale, respectively. In EFA, Kaiser-Meyer-Olkin (KMO) value was found to be 0.92 and the Bartlett Test result (912 91 = 6519.27, p <.00) was found significant. In addition, in original scale, a two-factor structure was found. This two factors solution explains 59.192% of the total variance. In CFA, factor structure of the scale was tested for two-factor solution as it was designed. According to the findings, it was found that the scale, containing 14 items with two sub-dimensions, had sufficient goodness of fit indices such as χ2/sd =1.344, RMSEA = 0.07, GFI = 0.97, CFI = 0.97, NFI = 0.90 and AGFI = 0.83. These goodness of fit indices shows that we have good model-data fit. The Stratified-alpha coefficient was found as 0.942 for the whole scale. Cronbach alpha coefficient was found as 0.935 and 0.805 for the awareness sub-dimension and exposure sub-dimension, respectively. As a result of the research, it was concluded that the Turkish version of the scale can be used as a valid and reliable measurement tool.